2018
DOI: 10.3390/su10124569
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9001 and Supply Chain Integration Principles Based Sustainable Development: A Delphi Study

Abstract: Driven by the increasing stakeholder and societal pressures, organizations and supply chains face the multi-dimensional challenges of not only integrating economic, environmental and social agendas into their management systems but also driving continual sustainability performance improvement. Aiming to support organizations in this sustainable development challenge, this paper explores the strategic management principles of ISO 9001 and supply chain integration from the lens of triple bottom line sustainabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 93 publications
1
34
0
1
Order By: Relevance
“…Similarly, the items related to Improvement (IMP), Evidence-based Decision Making (EDM), and Relationship Management (RM) loaded all together on the same construct. Hence, these QMPs were grouped together as a single construct named System Improvement (SI) [79], [80]. Finally, items related to Engagement of People (EP) and, Benefits (BEN) loaded on their corresponding factors without elements from other factors.…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…Similarly, the items related to Improvement (IMP), Evidence-based Decision Making (EDM), and Relationship Management (RM) loaded all together on the same construct. Hence, these QMPs were grouped together as a single construct named System Improvement (SI) [79], [80]. Finally, items related to Engagement of People (EP) and, Benefits (BEN) loaded on their corresponding factors without elements from other factors.…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…Delphi method had been used in many areas and can be used for any purpose requiring the use of committees [58][59][60][61][62]. Based on many studies, Sourani and Sohail (2015) presented Delphi as useful to (a) obtain accurate information that is unavailable, (b) handle complex problems that require more judgmental analysis, (c) define areas where there is considerable uncertainty and/or a lack of agreed knowledge or disagreement, (d) allow for combining fragmentary perspectives into a collective understanding, (e) model a real-world phenomenon involving a range of viewpoints and for which there is little established quantitative evidence, and (f) highlight topics of concern and assess uncertainty in a quantitative manner [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Purposesmentioning
confidence: 99%
“…More recently, Delphi has been widely used to develop the criteria and indicators in many fields, especially in construction fields [56][57][58][59][60][61][62]; for example, Sourani and Sohail (2015) [63] used the Delphi technique to develop an agreed set of economic sustainability criteria that should be addressed in a procumbent strategy. Moreover, many studies [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] have showed that Delphi can be useful to (a) obtain accurate information that is unavailable, (b) handle complex Sustainability 2019, 11, 3166 3 of 32 problems that require more judgmental analysis, (c) define areas where there is considerable uncertainty and/or a lack of agreed knowledge or disagreement, (d) allow for combining fragmentary perspectives into a collective understanding, (e) model a real world phenomena involving a range of viewpoints and for which there is little established quantitative evidence, and (f) highlight topics of concern and assess uncertainty in a quantitative manner. In particular, based on the summary explained in Appendix A [78][79][80][81][82][83][84], this research accordingly chose the Delphi technique to develop sustainable city indicators (SCIs) for Cambodia through three-round panel surveys.…”
mentioning
confidence: 99%
“…However, there have been limited studies on the indicators for CHT sustainability assessment. This study addresses this issue and identifies indicators by applying the Delphi method [57][58][59][60]. A total of 70 indicators were determined after three rounds of expert surveys.…”
Section: Theoretical Implicationsmentioning
confidence: 99%